RETHINKING KETENTUAN PERSENTASE SEBAGAI SYARAT PENCALONAN PRESIDEN DAN WAKIL PRESIDEN DI INDONESIA - I GUSTI NGURAH AGUNG SAYOGA RADITYA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Percentage provisions have a substantial part in the electoral law reform, especially for mathematical formulation. This research, that uses normative legal research method, showed that a legitimacy of percentage provision for candidacy requirement in President and Vice President Election is based on the legal authority of The House of Representatives. The 1945 Constitution of the Republic of Indonesia and most constitutions of other countries are not setting up a rigid formal requirement, like a minimum percentage, for presidential candidacy. A legal term has an important position in the making of law. A convention that uses “presidential threshold” as a term should be justified within a legal theoritical framework. Meanwhile, the perpetual discussion to create presidential system of government can works effectively, with a good support from the House of Representative, has always been a spirit but also a debatable material in every political acts in Indonesia. Legal formulation that used in Law No. 42-2008 must be viewed comprehensive so that justice and fairness in this political institutionalization process can be realized.